Digitalisasi pembiayaan mikro dan perlindungan harta (Hifdz al-mal): Studi kasus pada BMT NU Kalitidu - Shofa Robbani; Diah Dwi Rizki Putri Qomariyah; Muhammad Khoirul Anam; Reza Agustina; Neli Luluatul Isro’iyah (AL-Muqayyad, 2026)
This research is motivated by limited literature on BMT core system digitalization policies in mitigating financing risks and ensuring capital distribution for rural UMKM. This research gap underlines the urgency of analyzing the digitalization of BMT NU Kalitidu from a Maqasid Syariah perspective. The method used is descriptive qualitative through a case study design with primary and secondary data. Results show that adopting PT USID's centralized data architecture substantively enforces the pillar of hifdz al-mal (protection of wealth). Empirical achievements record up to 90% reduction in member complaints via WhatsApp Gateway and 100% financial track record detection accuracy during initial screening through SLIK OJK integration. This digitalization successfully deconstructs sociological nepotism bias into non-discriminatory, data-driven credit scoring to realize distributive justice. Another finding shows digital administration utilization for the naqlul yad contract in the agribusiness sector. Technology is concluded as a vital managerial instrument to actualize Maqasid Syariah values.